2016
DOI: 10.1093/bioinformatics/btw344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the molecule-based prediction of clinical drug responses in cancer

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 34 publications
0
117
0
1
Order By: Relevance
“…Molecular changes induced by treatment precede changes in morphology or these biomarkers, and may provide proximal endpoints of drug response40. The optical OSI from dual-mode images using metal complex-based probes captures these drug-induced changes in GSH and ROS, which have been hypothesized to correlate closely with treatment outcomes641.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular changes induced by treatment precede changes in morphology or these biomarkers, and may provide proximal endpoints of drug response40. The optical OSI from dual-mode images using metal complex-based probes captures these drug-induced changes in GSH and ROS, which have been hypothesized to correlate closely with treatment outcomes641.…”
Section: Discussionmentioning
confidence: 99%
“…For the GDSC dataset, raw gene expression data were downloaded from ArrayExpress (E-MTAB-3610) and response outcomes from https:/www.cancerrxgene.org release 7.0. Gene expression data of TCGA patients were downloaded from the Firehose Broad GDAC (version published on 28.01.2016) and the response outcome was obtained from (Ding et al, 2016). Patient datasets from clinical trials were obtained from the Gene Expression Omnibus (GEO), and the PDX dataset was obtained from the supplementary material of (Gao et al, 2015).…”
Section: Datasetsmentioning
confidence: 99%
“…Finally, each network was re-trained on the selected settings using the train and validation data together for each drug. We used Adagrad for optimizing the parameters of AITL and the baselines (Iorio et al, 2016) cell line Bortezomib targeted source 391 11609 GSE18864 (Silver et al, 2010) clinical trial Cisplatin Chemotherapy target 24 11768 GSE23554 (Marchion et al, 2011) clinical trial Cisplatin Chemotherapy target 28 11768 TCGA (Ding et al, 2016) patient Cisplatin Chemotherapy target 66 11768 GDSC (Iorio et al, 2016) cell line Cisplatin Chemotherapy source 829 11768 GSE25065 (Hatzis et al, 2011) clinical trial Docetaxel Chemotherapy target 49 8119 GSE28796 (Lehmann et al, 2011) clinical trial Docetaxel Chemotherapy target 12 8119 GSE6434 (Chang et al, 2005) clinical trial Docetaxel Chemotherapy target 24 8119 TCGA (Ding et al, 2016) patient Docetaxel Chemotherapy target 16 8119 GDSC (Iorio et al, 2016) cell line Docetaxel Chemotherapy source 829 8119 GSE15622 (Ahmed et al, 2007) clinical trial Paclitaxel Chemotherapy target 20 11731 GSE22513 (Bauer et al, 2010) clinical trial Paclitaxel Chemotherapy target 14 11731 GSE25065 (Hatzis et al, 2011) clinical trial Paclitaxel Chemotherapy target 84 11731 PDX (Gao et al, 2015) animal (mouse) Paclitaxel Chemotherapy target 43 11731 TCGA (Ding et al, 2016) patient Paclitaxel Chemotherapy target 35 11731 GDSC (Iorio et al, 2016) cell line Paclitaxel Chemotherapy source 389 11731 * Number of genes in common between the source and all of the target data for each drug (Duchi et al, 2011) implemented in the PyTorch framework, except for the method of (Geeleher et al, 2014) which was implemented in R. We used the author's implementations for the method of (Geeleher et al, 2014), MOLI, PRECISE, and ProtoNet. For ADDA, we used an existing implementation from https://github.com/jvanvugt/ pytorch-domain-adaptation, and we implemented the method of (Chen et al, 2017) from scratch.…”
Section: Does Aitl Outperform a Baseline For Inductive Transfer Learnmentioning
confidence: 99%
“…‱ Genomics of Drug Sensitivity in Cancer (GDSC) cell lines dataset (Iorio et al, 2016) ‱ Patient-Derived Xenograft (PDX) Encyclopedia dataset (Gao et al, 2015) ‱ TCGA patients with the drug response available in their records (Ding et al, 2016) ‱ TCGA patients without the drug response (Weinstein et al, 2013) The GDSC dataset (Yang et al, 2012;Iorio et al, 2016) has created a multi-omics dataset of more than a thousand cell lines from different cancer types, screened with 265 targeted and chemotherapy drugs. We use GDSC as the training dataset due to a high number of screened drugs.…”
Section: Datasetsmentioning
confidence: 99%
“…For in silico drug response prediction, translatability in the simplest case means that a model with good performance (e.g., high prediction accuracy) on in vitro datatrained on more samples compared to in vivo data-should also have good performance on in vivo data. The majority of studies suggest that gene expression data are the most effective data type for drug response prediction (Iorio et al, 2016;Geeleher et al, 2014;Ding et al, 2016;Graim et al, 2018). Geeleher et al (Geeleher et al, 2014) showed that a ridge regression model trained on GDCS gene expression data is translatable to Docetaxel, Cisplatin, Erlotinib, and Bortezomib clinical trial data.…”
Section: Introductionmentioning
confidence: 99%